The impact of implementing the women's reproductive rights agenda on climate change - Temmerman, Marleen; Peeters, Emilie; Delacroix, Celine; Arunda, Malachi; Khalid, Sara; Hanson, Claudia; Ojong, Samuel Akombeng (Frontiers in Global Women's Health, 2025)
The 1994 International Conference on Population and Development (ICPD) established sexual and reproductive health and rights (SRHR) as foundational to sustainable development. Thirty years later, advancing women's reproductive rights (WRR), encompassing agency, decision-making autonomy, and universal access to family planning—remains critical not only for health and gender equity but also for mitigating environmental degradation. By reducing unintended pregnancies and empowering women to align childbearing with personal and ecological capacity, WRR alleviates ecological stressors such as deforestation while enhancing health resilience in climate-vulnerable communities. Yet, despite well-documented linkages between population dynamics and environmental change, contemporary climate policies and funding mechanisms persistently exclude WRR. This oversight undermines the potential of reproductive justice to enhance climate resilience. Additionally, claims that integrating WRR into climate agendas covertly promotes population control or represses women in low- and middle-income countries are fundamentally misleading. Crucially, research is needed to quantify the specific environmental impacts of WRR, underscoring the urgent need for robust global models to predict and validate these co-benefits. Strengthening this evidence base is imperative to inform policies that integrate WRR indicators into climate financing frameworks, ensuring gender-responsive programming. Bridging this gap requires interdisciplinary collaboration to develop metrics that capture WRR's role in reducing resource consumption and enhancing adaptive capacity. Embedding WRR within climate agendas would harmonize reproductive justice with environmental action, unlocking synergies between gender equity, health resilience, and sustainability. Fulfilling the ICPD's vision demands centering WRR in global climate strategies, thereby advancing a just and livable future for all.